2016
DOI: 10.2174/1568026616666160215155347
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Fluorescent Bi2S3 Nanoparticles and their Application as Dual-Function SPECT-CT Probe for Animal Imaging

Abstract: Bismuth sulphide (Bi2S3) is an excellent semiconductor and its nanoparticles have numerous significant applications including photovoltaic materials, photodiode arrays, bio-imaging, etc. Nevertheless, these nanoparticles when fabricated by chemical and physical routes tend to easily aggregate in colloidal solutions, are eco-unfriendly, cumbrous and very broad in size distribution. The aim of the present manuscript was to ecologically fabricate water dispersible, safe and stable Bi2S3 nanoparticles such that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Diluted magnetic semiconductors (DMS) embedded in a glassy matrix, such as: Bi 2-x Mn x S3 [32], Bi 2-x Fe x S 3 , [33] Bi 2-x Co x S 3 [34] and Bi 2-x Cr x S 3 , [35] have potential properties for the production of photovoltaic cells [36,37] thermoelectric cooling, [38,39] photodetectors, [40] field emission electronics [41] and fluorescent markers [42].…”
Section: Chrome-doped Bi 2 S 3 Nanocrystals Embedded In Host Glass Matrixmentioning
confidence: 99%
“…Diluted magnetic semiconductors (DMS) embedded in a glassy matrix, such as: Bi 2-x Mn x S3 [32], Bi 2-x Fe x S 3 , [33] Bi 2-x Co x S 3 [34] and Bi 2-x Cr x S 3 , [35] have potential properties for the production of photovoltaic cells [36,37] thermoelectric cooling, [38,39] photodetectors, [40] field emission electronics [41] and fluorescent markers [42].…”
Section: Chrome-doped Bi 2 S 3 Nanocrystals Embedded In Host Glass Matrixmentioning
confidence: 99%
“…These Bi 2 S 3 NPs were also employed in small-animal single-photon emission computed tomography probes. 13 The synthesis of biomolecule-capped metal sulfides (such as CdS QDs, ZnS QDs, and CuS NPs) was reported previously. 14−16 Semiconductor NPs having biological cappings are gaining popularity as effective antibacterial agents with a broad variety of applications and biocompatibility, making them excellent candidates for pharmaceutical and biomedical use.…”
Section: Introductionmentioning
confidence: 99%
“…These Bi 2 S 3 NPs were also employed in small-animal single-photon emission computed tomography probes. 13 The synthesis of biomolecule-capped metal sulfides (such as CdS QDs, ZnS QDs, and CuS NPs) was reported previously. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…Uddin et al, synthesized a highly fluorescent, natural protein capped Bi 2 S 3 NPs by subjecting F. oxysporum to bismuth nitrate penta-hydrate, along with sodium sulfite under ambient conditions of pressure, temperature, and pH. It was found that they were fundamentally much more fluorescent than fluorophores (toxic fluorescent chemical compounds), which are largely utilized in immunohistochemistry, imaging, and biochemistry [48].…”
Section: Metal Sulfide Nanoparticlesmentioning
confidence: 99%
“…Additionally, F. oxysporum possessed significant industrial and biotechnological values as a wealthy source of diverse enzymes with wide applications such as cutinases, nitrilases, glycoside hydrolases (e.g., fucosidase, α-galactopyranosidases, and xylanases), fructosyl amino acid oxidase, laccases, lipoxygenase, nitric oxide reductase, decarboxylases, keratinase, phospholipase B, and triosephosphate isomerase [32][33][34][35][36][37][38][39][40][41][42]. Further, F. oxysporum is widely employed for the synthesis of different types of metal nanoparticles that could have various biotechnological, pharmaceutical, industrial, and medicinal applications [43][44][45][46][47][48][49][50][51][52][53][54][55]. The intensive literature search revealed the lack of review articles that deal with F. oxysporum particularly the bright side of this economically valuable fungus.…”
Section: Introductionmentioning
confidence: 99%